2008
DOI: 10.1038/cgt.2008.28
|View full text |Cite
|
Sign up to set email alerts
|

A dual role of p21waf1/cip1 gene in apoptosis of HEp-2 treated with cisplatin or methotrexate

Abstract: We investigated the effects of p21 waf1/cip1 gene overexpression in human laryngeal squamous carcinoma cells HEp-2 lacking p53protein expression on apoptosis induction upon the treatment with two commonly used chemotherapeutic agents, cisplatin and methotrexate. For that purpose, we employed cDNA arrays and qPCR to monitor gene expression upon treatment with AdCMV-p21 alone or in combination with the chemotherapeutic compounds. We found that p21 waf1/cip1 gene overexpression provoked apoptosis of HEp-2 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
(59 reference statements)
2
17
0
Order By: Relevance
“…Later, the implication of p21 in apoptosis was revealed. Previous reports indicate the contradictive effects of p21 on apoptosis: anti- and pro-apoptotic activities (24, 32), which might be influenced by several factors including the nature of the apoptotic stimuli (33), subcellular localization (34), and the extent of DNA damage (35). It was reported that human prostate cancer cell line LNCaP is resistant to docetaxel-induced apoptosis because docetaxel treatment results in the up-regulation of p53 and p21 proteins mediated by p38 phosphorylation, and that knockdown of p21 sensitizes LNCaP cells to docetaxel treatment (36).…”
Section: Discussionmentioning
confidence: 99%
“…Later, the implication of p21 in apoptosis was revealed. Previous reports indicate the contradictive effects of p21 on apoptosis: anti- and pro-apoptotic activities (24, 32), which might be influenced by several factors including the nature of the apoptotic stimuli (33), subcellular localization (34), and the extent of DNA damage (35). It was reported that human prostate cancer cell line LNCaP is resistant to docetaxel-induced apoptosis because docetaxel treatment results in the up-regulation of p53 and p21 proteins mediated by p38 phosphorylation, and that knockdown of p21 sensitizes LNCaP cells to docetaxel treatment (36).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is in line with the observation that p21 attenuates apoptotic signals in methotrexatetreated cells. 69 Of note, both methotrexate and FDH work in the same direction with regard to folate metabolism, inhibiting folate-dependent biosynthetic reactions. The activation of p21, however, is not sufficient to rescue cells from FDH-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous papers we showed that the both adenovirally mediated p53 and p21 overexpression inhibited the growth of several cell lines Kraljevic Pavelic et al 2008). However, p53 was more potent in growth inhibition and apoptosis induction of human tumor cells with non-functional p53.…”
Section: Introductionmentioning
confidence: 97%